Economic and Geographical Features of the Development and Location of the Textile Industry in Surkhandarya Region - Ergashev Sanjar Muhammadi O’g’li; Abdunazarov Husan Mengliyevich; Erdonov Muhammadi Nuralievich (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses the economic and geographical features of the development and location of the textile industry in Surkhandarya region, in which the share of cotton area and clusters is analyzed.